Wing measurements are a possible tool for the identification of European forensically important Sarcophagidae. (November 2022) - Szpila, Krzysztof; Johnston, Nikolas P.; Akbarzadeh, Kamran; Richet, Rene; Tofilski, Adam
Abstract: The flesh flies are a group of insects well known for their forensic importance. Reliable identification of these flies relies on the use of either molecular markers or the morphology of the male genital apparatus. Identification of female flesh flies is more time consuming and less reliable than their male counterparts. This is particularly problematic for forensic entomology practitioners, because female flesh flies are more abundant than males in carrion arthropod assemblages. As such, it is critical that alternative methods for flesh fly identification are established that are equally effective for both sexes. One promising technique is the use of wing measurements, which have been shown to be reliable for the identification of some groups of necrophagous Diptera from several geographical regions. We applied this method to the European Sarcophagidae for the first time, using a dataset of 881 specimens representing 29 species and 5 genera. Species identifications were based on 15 landmarks located at wing vein junctions. We also combined our results with data from previous studies of Calliphoridae and Muscidae which utilised the same methodology, enabling the testing of family level identification using wing morphometrics. Species identifications using wing measurements had varied success. While some species were successfully identified without error, others, particularly from the genus Sarcophaga, were often misclassified. Notably, in several species wing measurements successfully identified both males and females. The results presented here suggest that wing measurements are a promising complementary method to other methods for the identification of necrophagous Sarcophagidae especially in material unsorted at the family level. It can also be used to double check identification performed by a taxonomist using traditional methods. Highlights: Wing measurements can be used for discrimination of forensically important flies at the level of family and genus, however, at species level the results are variable. This method can be particularly useful for identification of large samples of females collected during succession studies. Methodology based on wing measurements can be used to all Calyptratae flies of forensic importance.